PENGEMBANGAN MODUL BERBASIS PEMBELAJARAN PEMAKNAAN PADA MATERI POKOK STRUKTUR ATOM - Novilia Novilia; Betty Holiwarni; Abdullah Abdullah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack : This reaserch development is aimed to developed a valid module based on eligibility content aspect, language, presentation, graphics and pemaknaan the topic of atomic structure. This reaserch method is research development (Research and Development, R & D) with 4-D development model with includes stages define phase, Design, Develop and Disseminate. Instruments of data collection are used validation and respons of teacher and student sheet. Data analysis technique is descriptive analysis, that way is calculate the avarage from every rating aspect in each aspect on module validation sheet. This research produce a module based on learning model of pemaknaan on the topic of Atomic Structure. The result show that module based on learning model of pemaknaan developed valid criteria based on eligibility content aspect, language, presentation, graphics and pemaknaanon with a precentage in a row 90,28%, 86,67%, 95%, 91,67%. The result of respons teacher and student about this module in a row 85,90% and 97,58% with very good criteriaKata Kunci : Module, Learning Model Of Pemaknaan, Atomic Structure